A numerical study on heat transfer and lubricant depletion on an anisotropic multilayer hard disk - Zeng, Yan (2013)
This paper presents a numerical investigation on the effect of thermal anisotropy of the top layer alloy on heat transfer and lubricant depletion on the disk surface in a heat-assisted magnetic recording (HAMR) system. The disk consists of multilayer structures and a thin layer of lubricant on the top surface. Cases under different laser powers and initial lubricant film thicknesses are examined. The top-layer alloy thermal anisotropy does show non-negligible effect on the heat transfer and lubricant depletion. With the top-layer alloy being more anisotropic, higher temperature increase and lager lubricant depletion can be observed on the disk surface. The results also show that the thermal anisotropy effect is more significant under a lower laser power but nearly keeps no much difference under different initial lubricant film thicknesses. Thus it is of importance to include the thermal anisotropy effect of the top-layer Co-alloy when simulating the heat transfer and lubricant depletion in practical multilayer HMAR systems, especially for the cases under the condition of lower laser power, as the effect cannot be neglected under such conditions.